ANTECEDENTS OF CONSUMER BUYING BEHAVIOR TOWARDS ON ENVIRONMENTALLY FRIENDLY PRODUCTS - Renny Risqiani Roesman (Universitas Trisakti, 2017)
This research aims to analyze the factors that influence the green purchase behavior. The sample used consisted of 163 respondents who were selected using purposive sampling. The Structural Equation Model method is used to analyze data using hypothesis testing. The results of the study show Attitude, Social Influence, Perceived Quality of Green Product have an effect on Green Purchase Behavior. Whereas environmental knowledge does not affect attitude and green purchase behavior. Management must be able to improve consumer shopping behavior by increasing Consumers Environmental Attitude, Social Influence and Perceived Quality of green products